Prevalence of tuberculosis among People Who Use Drugs 2000–2024: a systematic review and meta-analysis - Ngowi, W. S.; Mandizadza, O. O.; Wang, Minyan; Shao, W. T.; Ji, Conghua (Frontiers in Public Health, 2025)
BackgroundPeople who use drugs (PWUD) are at a higher risk of developing tuberculosis (TB); however, there is no clear evidence to determine the prevalence of TB in this group accurately. This study aimed to systematically review the prevalence of tuberculosis (TB) among PWUD across studies conducted in different countries.MethodsAn electronic search for original articles on the prevalence of TB among People Who Use Drugs (PWUD) was conducted in PubMed, Web of Science, and Science Direct. The reference lists of included studies were manually screened to identify omitted eligible studies. Extracted data were imported into a Microsoft Excel sheet. The random-effects model was employed to estimate the pooled prevalence of TB among People Who Use Drugs (PWUD), with effect size (ES) reported as point estimates and 95% confidence interval (CI). Subgroup analysis and sensitivity tests were also performed. All analyses were performed in STATA version 18.ResultsA total of 2,085 articles were retrieved from the search. After removing duplicates, screening titles and abstracts, and excluding non-eligible articles, 23 studies involving 164,121 patients met the inclusion criteria for the analysis. The average estimated prevalence of tuberculosis among People Who Use Drugs (PWUD) was 25% (95% CI: 0.21, 0.35). The prevalence of tuberculosis among PWUD was higher in Asia (32%) and North America (28%) compared to South America (10%) and Africa (5%). Additionally, the average prevalence of tuberculosis among PWUD was 36% in case-control studies, 26% in cohort studies, and 23% in cross-sectional studies.ConclusionThis review highlighted a high pooled prevalence of tuberculosis among People Who Use Drugs (PWUD), which varies across continents, study types, drug categories, and assessment tools. This emphasizes the need to integrate screening and prevention strategies into programs for PWUDs, address systemic inequities to reduce transmission, improve data reporting, and conduct more research in under-reported regions such as Africa and South Asia.Systematic review registrationidentifier CRD42024564181.